INTELLIGENCE QUALITY IN VERONICA ROTH’S ALLEGIANT - Allen Dicson Tampi; Gidion Maru; Imelda Lolowang (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
This study aims to determine the intelligence quality revealed in Veronica Roth's Allegiant. The author conducted this study using qualitative research based on Lincoln, and the data collection used two ways: Primary sources and secondary sources. The primary data collection was from the novel, and secondary data collection used references from articles, journals, books, and the internet. In analyzing the data, the author used a reader-response approach based on Cagri Tugrul Mart. The results of this study showed that Tris, the main character, used her intelligence qualities against the leader of the city of Chicago, Evelyn, and the leader of the Genetic Welfare Bureau, David. When Evelyn became the new city leader, the people expected her could stop the disputes between factions. However, Evelyn used her power for other purposes. Tris felt she had to do something to stop Evelyn from her act of cruelty that ruled over the city by unilateral decisions. In the end, they successfully stopped David and saved the city of Chicago